Laboratory investigation of carbonated BOF slag used as partial replacement of natural aggregate in cement mortars - Bodor, Marius; Santos, Rafael M; Cristea, Geanina; Salman, Muhammad; Cizer, Özlem; Iacobescu, Remus I; Chiang, Yi Wai; Van Balen, Koenraad; Vlad, Maria; Van Gerven, Tom (Cement and Concrete Composites, 2015)
Direct mineral carbonation produces a material rich in carbonates and with reduced quantities of free oxides. The aim of this work was to show that such materials can be used in the construction domain. Basic Oxygen Furnace (BOF) slag from the steelmaking process has been traditionally seen as unfit for bounded applications due to its propensity to swelling, resulting from hydration of its high free lime content. Here, BOF slag was crushed to suitable particle sizes, carbonated in an aqueous solution of carbonic acid, and utilized to replace 50% of natural sand aggregate in cement mortars. The mechanical and chemical properties of these mortars were compared to mortars containing non-carbonated slags, and a standard cement mortar as a reference. Tests were conducted to determine mortar paste consistency and soundness, and cured mortar compressive strength and leaching tendencies. The results showed a satisfactory performance for all considered aspects (comparable with the reference) of the mortar sample containing 37.5 wt% (1.5 in 4 parts solids) carbonated BOF slag of <0.5 mm particle size. KU Leuven Industrial Research Fund European Union Romanian Government “Dunarea de Jos” University of Galati Natural Sciences and Engineering Research Council of Canada